Cover Picture: Structural Simplification of Bedaquiline: the Discovery of 3‐(4‐(N, N‐Dimethylaminomethyl)phenyl)quinoline‐Derived Antitubercular Lead Compounds (ChemMedChem 2/2017). (20th January 2017) - He, Chunxian; Preiss, Laura; Wang, Bin; Fu, Lei; Wen, Hui; Zhang, Xiang; Cui, Huaqing; Meier, Thomas; Yin, Dali
Abstract : The front cover picture shows a molecular model of a bacterial rotary ATP synthase, which is targeted and inhibited by the novel antituberculosis (TB) drug Bedaquiline (Sirturo®), the first anti‐TB antibiotic compound in 40 years. Bedaquiline synthesis is expensive, mainly due to two chiral centers within the molecule. Using a fragment based synthesis approach He, Preiss et al. present an economical way of producing Bedaquiline derivatives with no chiral centers that still maintain antitubercular activity against Mycobacterium tuberculosis . More information can be found in the Full Paper by Huaqing Cui, Thomas Meier, Dali Yin et al. onpage 106 in Issue 2, 2017 (DOI:10.1002/cmdc.201600441 ). (The picture was drawn by Dr. Laura Preiss.)